Desarrollo de una propuesta de mejora para un sistema de potabilización de agua para el acueducto la venta el Cofre, Cajibío, Cauca (2019)
To carry out the development of a proposal for improvement for the system of water purification for the Venta el Cofre aqueduct in Cajibío, Cauca semade a thorough diagnosis of the plant, where the current state was evaluated, its infrastructure, the reagents used by it and the failures that They may be affecting the process. Water characterizations were taken before and after being treated by the aqueduct to know exactly what water parameters are being affected, and there are evidenced iron contents and turbidity are in a higher level of resolution 2115 of 2007 allows it. This led to the identification of the key points of the problem. The current dosage and a correction of this was done on a laboratory scale in the rainy seasons, additionally a proposal was made for a new filter bed since the current one was leaving sediment residues and prevented having an Optimum filtration with an efficiency of 48%. Therefore, tests were made experiments with water samples and three different types of filter beds in where the bed of fine sand, anthracite and gravel generates a new efficiency of 86% and It is considered as one of the best for the plant.